User Interface Redesign for the Course Card Filling Feature in the SIKAD Mobile Web Application using Goal-Directed Design Method - Handayani, Fitri; Wisudiawan, Gede Agung Ary; Adrian, Monterico (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The SIKAD mobile web application is a platform for an online-based Academic Information System developed by the Islamic University of Riau. The primary objective of this application is to facilitate various crucial processes such as Course Card Filling, printing of Study Result Cards, transcript printing, viewing payment history, and leave application. However, after conducting a usability evaluation using the System usability scale (SUS) involving 5 respondents, namely students of the Islamic University of Riau, it was found that the SUS score for this application was 60.0. Additionally, through interviews with the head of the development team and the respondents, issues were identified in the Course Registration interface which involved Course Card Filling and Course Card Printing feature. These issues were related to an untidy layout, unclear information, and inappropriate button placement on the screens of each respondent's device. Consequently, the user experience in using the SIKAD mobile web application was less satisfactory for the students. Therefore, the objective of redesigning the SIKAD mobile web application is to enhance the user experience in the Course Registration on the mobile platform and improve user satisfaction. The method employed for this redesign is Goal-Directed Design (GDD), which is suitable for meeting user needs and objectives. The redesigned interface will be evaluated using the System usability scale (SUS) to measure the extent to which the desired goals have been achieved. Through the GDD approach, it is anticipated that interface issues in this application can be addressed, and the set objectives can be fulfilled, resulting in an overall improvement in the usability of the SIKAD mobile web application.